The Pragmatics of Defendants’ Refusal Strategies in Saudi Courtroom Discourse - Alshammari, Bunder Sebail; Karam, Khaled Mostafa; Eissa, Mohamed (Corpus pragmatics : international journal of corpus linguistics and pragmatics, 2025)
This study investigates the refusal strategies employed by defendants in Saudi judicial discourse, drawing upon a corpus of official legal rulings issued by the Saudi Ministry of Justice. While previous pragmatic research has explored refusal strategies in educational and social contexts, little attention has been paid to their occurrence within legal settings, particularly in Arabic courtroom discourse. This study fills that gap by examining defendants’ responses to legal allegations through the lens of speech act theory and Beebe et al.’s (in: Scarcella, Andersen, Krashen (eds) Developing communicative competence in a second language, Newbury House, New York, pp 55–73, 1990) taxonomy of refusal strategies. A qualitative-quantitative analysis was conducted to categorize responses into direct performative, non-performative, and indirect strategies. The findings reveal that non-performative direct refusals were the most prevalent, followed by indirect strategies involving justification and rationalization. Performative refusals using explicit expressions were rare but significant in intent-driven contexts. This study contributes to legal pragmatics by demonstrating how defendants manage face-threatening acts through culturally and situationally adapted strategies. It highlights the role of performativity in legal discourse, where refusal operates as both a denial and a persuasive defense strategy. This underscores the importance of contextualized speech act analysis in judicial communication, offering implications for forensic linguistics, legal interpretation, and cross-cultural pragmatics.